2018
DOI: 10.1016/j.eclinm.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Global Prevalence of Asymptomatic Norovirus Infection: A Meta-analysis

Abstract: Background Studies about asymptomatic norovirus infections have been frequently reported. We aim to assess the global prevalence of asymptomatic infections. Method We identified publications that included the proportion of asymptomatic norovirus infections by searching in PubMed, Ovid, Scopus, and Web of Science and by screening references from the articles reviewed. The principal summary data were the prevalence of asymptomatic norovirus infection. Random-effect models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 22 publications
5
48
1
1
Order By: Relevance
“…It is known that norovirus outbreaks can be linked via asymptomatic patients. A meta-analysis of the global distribution of asymptomatic norovirus infections revealed that the prevalence rate in Europe was 18% (95% CI: 10–30%), when asymptomatic individuals were exposed under outbreak circumstances [ 29 ]. It has been discussed that GII.4 variants might originate from immunocompetent humans by inter-host transmission and the accumulation of mutations during the intra-variant periods [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that norovirus outbreaks can be linked via asymptomatic patients. A meta-analysis of the global distribution of asymptomatic norovirus infections revealed that the prevalence rate in Europe was 18% (95% CI: 10–30%), when asymptomatic individuals were exposed under outbreak circumstances [ 29 ]. It has been discussed that GII.4 variants might originate from immunocompetent humans by inter-host transmission and the accumulation of mutations during the intra-variant periods [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…HIE infection can now be used to reevaluate archived samples to better define parameters that would correlate with the infectious period of norovirus gastroenteritis to guide infection control. Of note, in a meta-analysis, the prevalence of norovirus RNA shedding from asymptomatic patients was estimated to be ≈9% ( 9 ). Moreover, in a large-scale study of outbreak data from CaliciNet (https://www.cdc.gov/norovirus/reporting/calicinet/index.html), a national norovirus surveillance network in the United States, the median C t value among asymptomatic patients was 28 ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, our results suggest the necessity of further analyzing the role of asymptomatic individuals in a community. Since the frequency of asymptomatic infection varies depending on the setting [5,12], analyses of individuals who are selected with an appropriate procedure with less bias are needed to verify the involvement of asymptomatic carriers in the latency and spreading of NV in the district and other settings.…”
Section: Plos Onementioning
confidence: 99%
“…Epidemiological studies have indicated that there are two NV-infected populations: one is AGE patients, and the other is individuals without diarrheal symptoms. The latter population, called "asymptomatic carriers" (which includes both pre-and post-disease-onset cases), is common worldwide [5,12]. The ratio of asymptomatic NV infections ranges from <1% to >30%, depending on the setting [5,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation